2012
DOI: 10.1007/bf03325329
|View full text |Cite
|
Sign up to set email alerts
|

Relation with HOMA-IR and thyroid hormones in obese Turkish women with metabolic syndrome

Abstract: The aim of this study was to investigate the relationship between insulin resistance and thyroid function in obese pre- and postmenopausal women with or without metabolic syndrome (MetS). 141 obese women were divided into two groups, HOMA-IR<2.7 and HOMA-IR>2.7, to evaluate relation with HOMA-IR and fatness, hormone and blood parameters. They were then divided into four groups as pre- and postmenopausal with or without MetS. Various fatness, hormone and blood parameters were examined. Statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
1
19
1
2
Order By: Relevance
“…In the studies examining TSH value and the existence of MetS, MetS parameters including obesity and MetS were reported to be more common particularly in patients with TSH value of >2.5 mU/L compared with those having lower TSH value (26). However, in our study, no significant relationship was detected between the presence of Mets and TSH level.…”
Section: Discussioncontrasting
confidence: 80%
“…In the studies examining TSH value and the existence of MetS, MetS parameters including obesity and MetS were reported to be more common particularly in patients with TSH value of >2.5 mU/L compared with those having lower TSH value (26). However, in our study, no significant relationship was detected between the presence of Mets and TSH level.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition to differences in adipose distribution, which also tend to affect hypertension, newly diagnosed hypertensives in the study had a large WC, high BMI, and high fasting glucose and insulin levels (28). On the other hand, thyroid hormone disorders are associated with changes in body composition, and obesity may have an impact on the levels of thyroid hormones as well as the risk of MetS in women (9,29). Tarcin et al (30) showed that MetS positive patients had significantly higher fasting glucose, triglyceride, fT4, BP, and lower HDL and fT3/fT4 ratio than MetS negative patients.…”
Section: Discussionmentioning
confidence: 87%
“…The association of obesity and IR is an extensive clinical condition, and insulin resistance (IR) also integrates these pathologies. Moreover, recent new studies have shown a relation between thyroid function tests and MetS parameters (9,10). The aim of our study was to explore the relationship or differences between anthropometric indices that assess central obesity and peripheral obesity, and the relationship among IR, MetS and thyroid function in female obese and healthy control subjects.…”
mentioning
confidence: 98%
“…Tiroid stimulan hormon (TSH) düzeyleri ile metabolik sendrom komponentlerinin ilişkisinin incelendiği çalışmalarda; özellikle TSH değerinin >2,5 mU/L olduğu hastalarda, düşük TSH dü-zeyine sahip hastalara göre, obezite dahil metabolik sendrom komponentlerinin ve metabolik sendromun daha sık görüldüğü saptanmıştır (9). Bu veriler, obezite ya da metabolik sendrom saptanan hastalarda tiroid fonksiyonlarının önemini göstermektedir.…”
Section: Discussionunclassified